A note on the vertex-switching reconstruction - I. Krasikov (International Journal of Mathematics and Mathematical Sciences)
Bounds on the maximum and minimum degree of a graph establishing its reconstructibility from the vertex switching are given. It is also shown that any disconnected graph with at least five vertices is reconstructible.